Rapid Determination of Catechin Content in Black Tea by Fluorescence Spectroscopy - Chenxu Du; Chaoqun Ma; Jiao Gu; Lei Li; Chun Zhu; Lvming Chen; Tingyu Wang; Guoqing Chen (Journal of Spectroscopy)
Catechin can effectively prevent the occurrence of cancers due to its strong antioxidant capacity. In this study, the catechin contents of black teas from 12 different regions of south China were investigated using fluorescence spectroscopy. Herein, the catechin contents of various black teas with constant concentration were determined at the optimal excitation and emission wavelength combining the standard addition method and fluorescence spectroscopy. The results indicated that there was a linear relationship between the obtained concentration and fluorescence intensity, where the R values were all greater than 0.99 and the limit of quantification (LOQ) was 0.02 μg/mL. Furthermore, the content of catechin monomer in the chlorophyll environment was measured under the same experimental conditions to demonstrate the correctness of the above experimental methods. It revealed that the experimental error was about 1.14% compared with the actual content. The current work was proved to be an efficient way to detect fluorescence spectrum through diluting the concentration of tea samples, thereby increasing the determination limit of catechin.